Evaluating the appropriateness and consequences of test use - Pan, Yi-Ching (Colombian Applied Linguistics Journal, 2009)
This paper addresses the issue of whether it is appropriate for universities or junior colleges to set foreign language proficiency requirements for graduation and offers a historical review of the relationship of test validity and test use. Examples of how to evaluate the appropriateness and consequences of test use are presented in order to discover what factors must be taken into account that contributes to the decision-making process. Finally, a model that specifies what evidence needs to be collected in support of a valid test decision is offered to help make decisions of test use more convincing and accordingly more beneficial to those individuals and groups who are affected by the tests.